Comprehensive Evaluation of Nurses' Competencies and Performance in Hospital Infection Control Practices: A Case Study of Ali Abad Teaching Hospital, Afghanistan - Nooriyan, Abdul Aziz; Khanjari, Hakimullah; Enayat, Enayatullah (Journal of Health Science and Medical Therapy, 2025)
Hospital-acquired infections (HAIs) remain a significant public health concern, posing challenges to healthcare systems worldwide. Nurses, as frontline healthcare workers, play a critical role in preventing and controlling these infections. However, their knowledge and practices regarding infection prevention and control are often inconsistent, which can lead to varying levels of infection prevention. The primary aim of this study was to assess the awareness, attitudes, and practices of nurses at Aliabad Teaching Hospital in Kabul, Afghanistan, concerning hospital-acquired infections. A descriptive cross-sectional study was conducted over a three-month period, involving 150 nurses working in different departments of the hospital. Data was collected through a structured questionnaire that assessed demographic information, awareness, attitudes, and practices related to infection prevention. The study found that a significant majority of nurses (81.36%) were aware of HAIs, but only 42.5% reported possessing the necessary skills to manage these infections effectively. Nurses who received regular training and used personal protective equipment (PPE) exhibited higher levels of competency in infection control practices. However, there were areas where improvement was needed, particularly in hand hygiene practices and consistent use of PPE. The study concluded that while there is a general awareness of HAIs among nurses, there is a need for continuous training and strengthening infection control measures to enhance patient safety and improve healthcare outcomes.